Limited Awareness and Financial Intermediation - Sarah Auster; Nicola Pavoni (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
We study the market interaction between financial intermediaries and retail investors, who not only face uncertainty about the performance of the different investments but also have limited awareness of the available investment opportunities. Intermediaries compete for investors via the menu of investment options they offer. We show that when competition is limited, intermediaries restrict their offers to extreme options, e.g. very risky and very safe products. We also consider investor heterogeneity and show that the presence of sophisticated, fully aware investors can impose a negative externality on investors with limited awareness. Self-reported data from customers in the Italian retail investment sector support the key predictions of the model: the menus offered to less knowledgable investors contain few products, most of them are nevertheless perceived to be at the extremes.
Keywords: D82; D83; G24; 330; Unawareness; financial investments; delegation